Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005186.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve hand hygiene compliance in patient care

Abstract: This is the published version of the paper. This version of the publication may differ from the final published version. Permanent repository link: https://openaccess.city.ac.uk/id/eprint/20266/ Link to published version: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…We included eight reviews on interventions to promote safety culture in health facility with a median AMSTAR score of 5.5; four reviews focused on administration of preventive influenza vaccination to healthcare workers and its effectiveness and uptake [44-47], one on hand hygiene promotion [48], one on the impact of interventions to reduce medication related errors [49] while two of the reviews reported the impacts of multi-component safety culture strategies and organizational interventions [50,51]. None of the reviews reported MNH specific outcomes while meta-analysis was conducted in two of the reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included eight reviews on interventions to promote safety culture in health facility with a median AMSTAR score of 5.5; four reviews focused on administration of preventive influenza vaccination to healthcare workers and its effectiveness and uptake [44-47], one on hand hygiene promotion [48], one on the impact of interventions to reduce medication related errors [49] while two of the reviews reported the impacts of multi-component safety culture strategies and organizational interventions [50,51]. None of the reviews reported MNH specific outcomes while meta-analysis was conducted in two of the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacist-led interventions aimed to reduce drug-related morbidity, hospitalization or death from medication overuse or misuse in healthcare facility have shown significant impact on reducing hospital admissions (RR: 0.64, 95% CI: 0.43, 0.96) although the evidence is weak and does not report impact on preventable drug related morbidity [49]. Various safety culture strategies and interventions to improve hand hygiene compliance reported insufficient evidence to draw any firm conclusion [48] with some evidence of improved perceptions and potentially reduced patient harm [50,51]. …”
Section: Resultsmentioning
confidence: 99%
“…The WHO recommends undertaking hand hygiene when entering the patient environment. However as staff compliance with hand hygiene is routinely less than 100% [11], introduction of microbes into bed spaces is still a risk. Accordingly, optimising ward design to limit the risk of contamination, is still of value.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare worker (HCW) hand hygiene is considered to be one of the most important interventions for the prevention of HAIs and AROs [4,5]. However HCW hand hygiene is typically poor, with a median compliance of 40% [6], and few interventions have been demonstrated to result in significant and sustained improvement [4,5,7]. Currently, ‘multimodal’ hand hygiene programs are recommended, including education, improved access to alcohol-based hand sanitizer, workplace reminders, and regular and sustained audit and feedback of hand hygiene compliance [4,5,8].…”
Section: Introductionmentioning
confidence: 99%